Effects of Newcastle Disease Virus Strains Af 2240 and V4-Upm on Cytolysis and Apoptosis of Leukemia Cell Lines - Al-Absi, Aied Mohammed (2008)
Newcastle disease virus (NDV) is a member of the Paramyxoviridae that has caused severe economic losses in the poultry industry worldwide. Several strains of NDV were reported to induce cytolysis to cancerous cell lines. In this study, two NDV isolates namely, AF 2240 and V4-UPM were evaluated for their anti-leukemic properties against four leukemic cell lines - HL60 (Promyelocytic leukemia), WEHI 3B (Mouse myelomoncytic leukemia), CEMSS (Human T-lymphobalstic leukemia) and K562 (Erythromyelobalstic leukemia). The cytolytic effects of NDV strains AF 2240 and V4-UPM towards WEHI 3B, HL60, CEMSS and K562 cell lines were determined using microtetrazolium (MTT) assay. The cytolytic dose - fifty percent (CD50) for WEHI 3B, HL60 and CEMSS treated with AF 2240 strain were 2, 25, 16 HAU, respectively, while the CD50 for WEHI 3B, HL60 and CEMSS treated with V4-UPM were 8, 110 and 64 HAU, respectively. Comparatively, both NDV strains showed very low cytolytic activity against K562 and non-leukemic cell lines namely, 3T3 (mouse fibroblasts), mouse lymphocytes and human peripheral lymphocytes. Further studies were done to observe the morphological changes in the WEHI 3B treated cells using light, transmission and scanning electron microscopes. The apoptosis and necrosis were examined under fluorescence microscope, where the cells were stained with acridine orange (AO) and propidiun iodide (PI). The treated cells with NDV strains AF 2240 and V4-UPM showed apoptotic features such as cell shrinkage, cell blebbing, and formation of apoptotic bodies compared to the control cells that did not express any features for apoptosis and necrosis. The early apoptosis was also observed under fluorescence microscope, where the cells were stained with Annexin V and PI. The virus effect on cell proliferation was determined by MTT assay and BrdU techniques. Furthermore, at molecular level, both NDV strains caused internucleosomal DNA cleavage producing a multiple of 180-200 bp fragments, that were visible as a ladder on the agarose gel. Early apoptosis was also observed using Annexin V flow cytometry method. The percentage of apoptosis for WEHI 3B cells treated with NDV strains AF 2240 and V4-UPM had increased with time. Cell cycle and apoptosis were also determined using flow cytometry PI method. Both NDV strains were not able to arrest WEHI 3B at specific cell cycle phases using flow cytometry PI method. In this study anti-leukemic activity of both NDV strains was evaluated on BALB/c mice induced leukemia with WEHI 3B cells. A day later they were treated with NDV strains AF 2240 and V4-UPM and arabinocytocine, a commercial drug, as positive control. The mice groups treated with arabinocytocine, NDV strains AF 2240 and V4-UPM showed significant killings (p<0.05) of leukemic cells compared to the mice group without any treatment. The total white blood cell and percentage of blasts cell in the blood, bone marrow and spleen smears were significantly low (p<0.05) in mice treated with the arabinocytocine, NDV strains AF 2240 and V4- UPM compared to the mice group without treatment, that showed high number of leukemia. Spleen and liver weights were significantly low (p<0.05) in the mice groups treated with arabinocytocine, NDV strains AF 2240 and V4-UPM compared to the mice group without treatment, that showed significant (p<0.05) splenomegaly and hepatomegaly. Histopathological studies carried out had confirmed haematological results. From the results obtained, the mice groups treated with both NDV stains AF 2240 and V4- UPM showed similar results as arabinocytocine, which is a commercial drug for leukemia. Immunoperoxidase staining, haemaggulatintion test and real time PCR were carried out to detect NDV in mice organs after treatment with NDV. The results showed no NDV particles were detected in the organs. This study showed that NDV strains AF 2240 and V4-UPM had caused cytolytic effects against WEHI 3B leukemia cell line in vitro and in vivo.